Penyebaran Varietas Unggul Kedelai dan Dampaknya terhadap Ekonomi Perdesaan - Krisdiana, Ruly (Jurnal Penelitian Pertanian Tanaman Pangan, 2014)
Improved soybean varieties are generally possessing high yield, resistant to major pests and diseases, and carrying other important properties. Until 2013 more than 70 improved varieties had been released, but not all are planted by farmers. The present research objectives were: (1) to identify the distribution and farmers preferences of improved soybean varieties, (2) to identify the adoption barrier of new soybean varieties, and (3) to estimate the economic contribution of the new soybean varieties. The study was conducted on soybean production centers in Indonesia, covering East Java, Central Java, West Nusa Tenggara, Nanggroe Aceh Darussalam, West Java, and South Sulawesi. The research was carried out using survey method, where samples of farmers were used as sources of the primary data. There were total of 600 farmer respondents. Analyses of the data applied the tabulation analysis, principal components analyses, and contributions analyses. The results showed that soybean varieties most widely adopted by farmers in order of the highest were: Anjasmoro (32.1% farmer users, covering area of 190,567 ha), Willis (17.9% farmer users, area of 93,187 ha), Mahameru (9.1% farmer users, area of 78,190 ha), Grobogan (11.2% farmer users, area of 71,576 ha). Farmer’s preferences to soybean variety, included the following characters: flowering at 35-40 days after planting, harvesting 70-75 days after planting, stem with many branches, yellow seed coat color, round seed shape, large seed size, and the grains sold easily. The reason of varieties was not being adopted by farmers include: unavailability of seeds at planting time, seed size was too small, seed price is too expensive, and the distance from farmers’ home to the seed kiosk was too far away. The economic contribution of improve soybean varieties was as followed: Anjasmoro (Rp 1.3 trillion), Mahameru (Rp 0.61 trillion), Grobogan (Rp 0.61 trillion), Willis (Rp 0.56 trillion), Baluran (Rp 0.25 trillion), while the other improved varieties (Argomulyo, Bromo, Orba, Kipas Merah, Galunggung, Kipas Putih, Davros, Gepak kuning, Gepak Hijau, Malabar, Burangrang, Mitani, Kaba, Lokon, Sinabung) each contributed to the rural economy in a total of Rp 0.57 trillion. The total economic contribution of all improved soybean varieties was estimated at Rp 3.9 trillion.